1997
DOI: 10.1021/cm960440i
|View full text |Cite
|
Sign up to set email alerts
|

Bridged Bisimide Polysilsesquioxane Xerogels:  New Hybrid Organic−Inorganic Materials

Abstract: New hybrid organic−inorganic materials which incorporate the bisimide functionality were synthesized by sol−gel condensation of bisimide monomers containing pendant triethoxysilyl groups. Monomers were prepared by transimidation of bis (2-aminopyridyl)imides with (3-aminopropyl)triethoxysilane. This synthesis was applicable to a variety of commercially available bisanhydrides and did not result in the evolution of water which causes premature hydrolysis and condensation of the trialkoxysilyl group. Solid-state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 44 publications
0
52
0
Order By: Relevance
“…[34] Finally, Shea et al have demonstrated that the hardnesses measured for bridged bisimide polysilsesquioxane xerogels were intermediate between nylon-6 and SiO 2 . [35] While these studies empirically confirm that incorporation of organic moieties into sol-gel glasses can reduce their brittleness, no models were presented to rationalize the contribution of the organic substructure to the mechanical properties. In this study, the contribution of the organic bridge to the oxycarbosilanes fracture resistance is estimated and the results are reported in table 1.…”
mentioning
confidence: 98%
“…[34] Finally, Shea et al have demonstrated that the hardnesses measured for bridged bisimide polysilsesquioxane xerogels were intermediate between nylon-6 and SiO 2 . [35] While these studies empirically confirm that incorporation of organic moieties into sol-gel glasses can reduce their brittleness, no models were presented to rationalize the contribution of the organic substructure to the mechanical properties. In this study, the contribution of the organic bridge to the oxycarbosilanes fracture resistance is estimated and the results are reported in table 1.…”
mentioning
confidence: 98%
“…The observation that incorporation of organic moieties into sol-gel glasses can reduce their brittleness [156][157][158][159][160] has drawn the attention of the semiconductor industry. However, in order to be viable candidates for application in the BEOL, the silicon precursors to these hybrid materials should be low cost, commercially available or readily prepared on a large scale.…”
Section: Hybrid Organic-inorganic: Oxycarbosilanesmentioning
confidence: 99%
“…Furthermore, inhomogeneous dispersion of two phases and leaching of the photoactive molecules frequently occur in this sort of hybrid materials for which the concentration of luminescent centers is also largely decreased. In this way, a few novel studies in terms of the covalently bonded hybrids have appeared and the as-derived molecular-based materials exhibit monophasic appearance even at a high concentration of metal complexes [12][13][14][15][16][17][18][19][20][21][22][23][24] co-workers have been concentrated on complexes of rare earth-pyridine-dicarboxylic acid or their derivatives and the molecular-based dicarboxylic acid derivative materials have exhibited strong emissions. Zhang et al started to modify 1,10-phenanthroline and di-pyridine in order to prepare the determined molecular-level hybrid materials [12,13].…”
Section: Introductionmentioning
confidence: 99%